Quality services for students in learning through information technology - Adam, Zalika; Che Ibrahim, Khairani (2009)
Building a culture of learning within today’s classrooms requires teachers and students to jointly engaged in teaching and learning. Learning through Information Technology (IT) has been highlighted as an effective approach to quality of learning. Information Technology Services are one of component used by students for their study. This is because by using IT Services in their study, the students feel that their study becomes easier and interesting. Hence, quality services in IT are needed most in the globalization era. The main objective of this study to show beneficial services through IT that prepared for IIUM students during their study. The study used simple random sampling survey distributes for 55 IIUM students for those used IT services during their learning. Conclusion of this study found that the University needs to facilitate so that the student can gain more access to the information. In addition, our research suggests the need for some type of 'one-stop centre' for information on education and training on IT services. This would greatly improve the ability of student to access and make use of all IT services in the campus.